Look-up table based fuzzy controller in order to control steaming room process - Aminifar, Sadegh; Mohamad Kekshar, Sirwan; Daneshwar, Muhammadamin (Innovaciencia, 2018)
Introduction: In this paper, using look-up table control strategy, a fuzzy logic controller is designed for controlling the temperature of steaming room in terrazzo tile plant corresponding to dedicated process diagrams. Methods: In the proposed method, the temperature and error of temperature are considered as inputs to control the duration of valve open time to decrease the activation times of valves in order to increase their longevity. The strategy considers an off-line trained look-up table for setting the time of opening valve in the specific temperature. A fuzzy controller with fifteen extracted rules is designed for controlling the duration of valve open time. Results: Results show that the number of switching of valve reduces compare to intuitionistic or expert rule extraction. Conclusions: Simulations provide more compatible steaming process rout compare to PID controllers.